Humoral immune response to selective mycobacterial antigens and serodiagnosis of active tuberculosis in Bangladeshi patients - Mohiuddin, Md.; Haq, J. Ashraful (IMC Journal of Medical Science, 2017)
Background and objective: Serological test has become an important tool in the diagnosis of TB cases. This study focused on the analysis and comparison of antibody response to two Mycobacterium tuberculosis (MTB) antigens namely Ag85 complex and culture filtrate protein (CFP) in patients with tuberculosis. Antibody response to specific antigen was utilized as a diagnostic tool to detect active tuberculosis (TB) cases. Methods: Sera from 30 patients with active tuberculosis and 30 healthy individuals were tested by enzyme linked immunosorbent assay (ELISA) for the presence of immunoglobulin (Ig) G and IgM antibodies against Ag85 complex and culture filtrate protein (CFP) antigens of MTB. Results: The mean OD values of serum IgM and IgG antibodies against Ag85 and CFP were significantly (p<0.0001) higher in patients than that of healthy control individuals. Among the 30 tuberculosis patients, anti-Ag85 complex IgM and IgG was positive in 66.7% and 70.0% patients respectively. The seropositive rate of anti-CFP IgM and IgG was 33.3% and 56.7% respectively. The sensitivity and specificity of anti Ag85 and anti-CFP IgM and IgG ranged from 60.0% to 96.7%. Conclusion: The study demonstrated that determination of IgM and IgG antibodies against Ag85 complex and CFP could be used as a serological marker for diagnosis of active tuberculosis. IMC J Med Sci 2016; 10(2): 53-57